Analysis Of Factors Of Healthy Latrine Ownership In The Tamansari Health Center Area In 2024 - Damayanti, Rika; Harmendo; Murniani (Biro Akademik, Penelitian dan Pengabdian kepada Masyarakat, Universitas Anak Bangsa, 2024)
This study aims to identify factors related to the ownership of healthy latrines in the working area of the Tamansari Health Center, Pangkalpinang City in 2024. The method used was a quantitative approach with a cross-sectional design, involving 106 respondents from three villages. The results of the analysis showed that there was a significant relationship between the ownership of healthy latrines and the role of health workers (p=0.003; POR=4,254), knowledge (p=0.000; POR=9.494), attitude (p=0.046; POR=2,440), land availability (p=0.000; POR=5.684), and revenue (p=0.003; POR=4,429). However, no significant relationship was found between education and healthy latrine ownership (p=0.561). Community knowledge has proven to be the dominant factor affecting the ownership of healthy latrines. These findings emphasize the importance of increasing knowledge and the role of health workers in encouraging people to have healthy latrines, as well as the need for better interventions in proper sanitation access.